Youth victims of community violence: developmental outcomes and prevention challenges - Caridade, Sónia (2020)
This work was financed by National Funds through FCT (Foundation for Science and Technology) under the project LookCrim - Looking at Crime: Communities and Physical Spaces - PTDC/DIR-DCP/28120/2017 and within the framework of the CIEC (Research Center for Child Studies of the University of Minho) project under the reference UID/CED/00317/2019.